1999
DOI: 10.1093/hmg/8.6.1077
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense and temperature-sensitive mutations in PEX13 are the cause of complementation group H of peroxisome biogenesis disorders

Abstract: Peroxisome biogenesis disorders, including Zellweger syndrome (ZS), neonatal adrenoleukodystrophy (NALD) and infantile Refsum disease, are lethal hereditary diseases caused by abnormalities in peroxisomal assembly. To date, 12 genotypes have been identified. We now have evidence that the complete human cDNA encoding Pex13p, an SH3 protein of a docking factor for the peroxisome targeting signal 1 receptor (Pex5p), rescues peroxisomal matrix protein import and its assembly in fibroblasts from PBD patients of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…In previous studies, we revealed the restoration of peroxisomes in a temperature-dependent manner in the fibroblasts of patients with milder types of PBD, those with all types of IRD, and some with the NALD phenotype in CG-E (CG1), CG-A (CG8), CG-F (CG10), and CG-H. In addition, we demonstrated ts mutations that cause this phenomenon in IRD and NALD patients with CG-E (CG1), CG-F (CG10), and CG-H; G843D in PEX1, E55K in PEX2, and I326T in PEX13, respectively (18,23,24). We have now identified a missense mutation in PEX6 from a NALD patient with CG-C (CG4) whose fibroblasts revealed the same ts phenotype.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…In previous studies, we revealed the restoration of peroxisomes in a temperature-dependent manner in the fibroblasts of patients with milder types of PBD, those with all types of IRD, and some with the NALD phenotype in CG-E (CG1), CG-A (CG8), CG-F (CG10), and CG-H. In addition, we demonstrated ts mutations that cause this phenomenon in IRD and NALD patients with CG-E (CG1), CG-F (CG10), and CG-H; G843D in PEX1, E55K in PEX2, and I326T in PEX13, respectively (18,23,24). We have now identified a missense mutation in PEX6 from a NALD patient with CG-C (CG4) whose fibroblasts revealed the same ts phenotype.…”
mentioning
confidence: 67%
“…In humans, defective peroxisomal metabolic functions result in ZS, NALD, and IRD, collectively referred to as PBD, which are genetically classified into at least 12 CG (2). Ten causative genes (PEX) have been cloned: PEX1, PEX2, PEX5, PEX6, PEX7, PEX10, PEX12, PEX13, PEX16, and PEX19, corresponding with CG-E (CG1), CG-F (CG10), CG2, CG-C (CG4), CG11, CG-B (CG7), CG3, CG-H, CG-D (CG9), and CG-J in humans, respectively (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). ZS patients have profound dysmorphic features, skeletal abnormalities, renal cysts, and severe progressive neurologic and hepatic disease and, therefore, rarely survive early infancy.…”
mentioning
confidence: 99%
“…Biochemical analyses including fatty acids indicated peroxisomal abnormalities (C24:0/ C16:0: 0.15; normal control: 0.58), but dihydroxyacetone phosphate acyltransferase activity was normal in the patient's fibroblasts (patient: 2.26; control: 1.55 nmol/mg/120 min) (8).…”
Section: Patientmentioning
confidence: 92%
“…The patient with the milder form, NALD, had a missense mutation with substitution of isoleucine (Ile) 326 by threonine (Thr), I326T, within a SH3 domain, and showed normal development just before a sudden deterioration with a high fever due to a respiratory infection. Additionally, the patient's fibroblasts showed a TS phenotype in peroxisome assembly and function (8).…”
mentioning
confidence: 97%
See 1 more Smart Citation